2021
DOI: 10.1101/2021.04.28.21256237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cost-effectiveness of COVID-19 vaccination in low- and middle-income countries

Abstract: SummaryDespite the advent of safe and highly effective COVID-19 vaccines1–4, pervasive inequities in global distribution persist5. In response, multinational partners have proposed programs to allocate vaccines to low- and middle-income countries (LMICs)6. Yet, there remains a substantial funding gap for such programs7. Further, the optimal vaccine supply is unknown and the cost-effectiveness of investments into global vaccination programs has not been described. We used a validated COVID-19 simulation model8 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…High COVID-19 vaccine coverage in low- and middle-income countries is likely to be extremely cost-effective and save millions of lives. 4 There are however major global inequities in access to COVID-19 vaccines, 5 , 6 and gaps in our knowledge of factors likely to be associated with COVID-19 vaccine uptake and acceptability, which has primarily come from high-income countries. 7 , 8 The scant literature about COVID-19 vaccination from Africa to date has focused on COVID-19 vaccine acceptability and hesitancy rather than actual vaccination behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…High COVID-19 vaccine coverage in low- and middle-income countries is likely to be extremely cost-effective and save millions of lives. 4 There are however major global inequities in access to COVID-19 vaccines, 5 , 6 and gaps in our knowledge of factors likely to be associated with COVID-19 vaccine uptake and acceptability, which has primarily come from high-income countries. 7 , 8 The scant literature about COVID-19 vaccination from Africa to date has focused on COVID-19 vaccine acceptability and hesitancy rather than actual vaccination behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Also, our study has a variety of outcomes incorporated and reported, beyond Our work is in line with most economic evaluations of COVID-19 vaccination performed to date, either in peer-reviewed articles 5 6 7 8 9 10 11 12 13 32 , or pre-print. 4 In all of them, vaccination is shown to be either cost-effective -using commonly-used cost-effectiveness thresholds-or directly cost-saving. Usually, health technologies are initially available at a higher cost than in later periods 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination for the recent SARS-CoV-2 pandemic has generally been implemented without formally assessing this dimension, given the global emergency it caused. More recently, several cost-effectiveness analyses of COVID-19 vaccination have been published [4][5][6][7][8][9][10][11][12] , most of them focused on high-income countries and only one with a speci c focus on a Latin American country 13 .…”
Section: Introductionmentioning
confidence: 99%
“…They are the basis for overall planning and implementation of activities in individual countries, e.g., [21]. The prices and methods of vaccine distribution that differ between countries depending on their affluence have become an important issue [22,23]. Vaccination strategies are analyzed from multiple global and local perspectives and concerning various parameters such as population specifics, vaccine availability, vaccination logistics, etc.…”
Section: Positioning Of the Papermentioning
confidence: 99%